PENGARUH DISIPLIN KERJA, MOTIVASI KERJA, DAN STRES KERJA TERHADAP KINERJA PERANGKAT DESA SE-KECAMATAN REMBANG - Muhammad Fahmi Jalu Andika; Syaiko Rosyidi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Rembang District has 27 villages, to realize good administration of the village requires good performance from the village apparatus. The purpose of this study is to provide information on how the performance of village apparatus is influenced by work discipline, work motivation and work stress. This study uses a quantitative research type with a survey using a questionnaire. This study involves two types of variables. The variables of work discipline, work motivation as independent variables, while performance as the dependent variable. Research data were obtained directly without intermediaries. The population of this study was village apparatus throughout Rembang District with a population of 232 people. The sampling technique used the entire population, but the final number of samples was 170 people because 62 people were unwilling to be research subjects. The analysis techniques used were instrument tests, hypothesis tests and determination tests. The findings of this study were that the variables of work discipline and work motivation had a significant effect on the performance of village apparatus, while the work variable did not affect the performance of village apparatus.